Similar but different? Comparing economic policy responses to the Corona Crisis in the UK and Germany - Bob Hancké; Toon Van Overbeke; Dustin Voss (London School of Economics and Political Science (LSE), European Institute, 2021)
This paper presents a comparative political economic analysis of the policy responses to the Covid-19 crisis in Germany and the UK. These two countries responded to this symmetric economic shock with similar furlough and business loan schemes to stabilize both the demand and supply side of the economy. However, highly different political-economic structures in both countries meant these a priori similar policies produced different results. We argue that this divergence can best be explained through the lens of Varieties of Capitalism's 'institutional complementarities'.
Keywords: 330; political economy; economic policy; Europe